In-vitro glistening formation in six different foldable hydrophobic intraocular lenses - Tandogan, Tamer; Auffarth, Gerd U.; Son, Hyeck Soo; Merz, Patrick; Choi, Chul Y.; Khoramnia, Ramin (BMC ophthalmology, 2021)
Glistenings describe small, refractile microvacuoles that may arise within the intraocular lens (IOL) material and reduce the patients’ quality of vision. Lenses composed of hydrophobic acrylic material are particularly affected by glistening formation. In this study, we compared the tendency of glistening formation in six different types of hydrophobic acrylic intraocular lenses (IOLs).